2014
DOI: 10.1371/journal.pbio.1001808
|View full text |Cite
|
Sign up to set email alerts
|

Brain Endothelial Cells Control Fertility through Ovarian-Steroid–Dependent Release of Semaphorin 3A

Abstract: Endothelial-cell–derived Sema3A promotes axonal outgrowth and plasticity and thereby regulates neurohormone release in the adult rodent brain in response to the ovarian cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 63 publications
2
64
0
Order By: Relevance
“…A study from our group has shown that in the adult rodent brain, vascular endothelial cells of the ME express and release Sema3A (fig. 4b-d) and that the amount released is regulated by the ovulatory cycle [132]. In particular, this study highlights a new mechanism through which the fenestrated endothelial cells of the ME release the 65-kDa isoform of Sema3A (p65-Sema3A) with precise timing during the ovarian cycle, being maximal during proestrus under the influence of circulating estradiol (E 2 ), and that Nrp1 is expressed in GnRH axons.…”
Section: Semaphorins and Neuroglial Plasticity In The Adult Hypothalamentioning
confidence: 97%
See 1 more Smart Citation
“…A study from our group has shown that in the adult rodent brain, vascular endothelial cells of the ME express and release Sema3A (fig. 4b-d) and that the amount released is regulated by the ovulatory cycle [132]. In particular, this study highlights a new mechanism through which the fenestrated endothelial cells of the ME release the 65-kDa isoform of Sema3A (p65-Sema3A) with precise timing during the ovarian cycle, being maximal during proestrus under the influence of circulating estradiol (E 2 ), and that Nrp1 is expressed in GnRH axons.…”
Section: Semaphorins and Neuroglial Plasticity In The Adult Hypothalamentioning
confidence: 97%
“…g Quantitative analysis of the percentage of GnRH nerve terminals located <1 μm from the pericapillary space in the external zone of the ME in explants from diestrous (left panel) and proestrous (right panel) rats treated with Sema3A, a Nrp1-neutralizing antibody (Nrp1-Ab) and in controls. Illustrations in b-g were adapted with permission from Giacobini et al [132]. h Schematic highlighting morphological changes in GnRH terminals and tanycytic end feet during the different phases of the ovulatory cycle.…”
Section: Semaphorins and Neuroglial Plasticity In The Adult Hypothalamentioning
confidence: 99%
“…The present study implicated the synergistic role of Nrp1 in DDR2-induced osteoblastogenesis. Together with other commence in teeth formation [31,32], wound healing [33,34], and regulation of reproductive cycle [35,36,37], it could be deduced that DDR2 and Nrp1 are not only structurally but also functionally related proteins. It is probably that DDR2 also forms complex with Nrp1 and this two molecules act in concert with each other in other aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the similar structural characteristics, Nrp1 has functions in common with DDR2, such as roles in angiogenesis [28,29,30], teeth formation [31,32], wound healing [33,34], and female reproductive cycle [35,36,37]. In this study, we aimed to examine the function of Nrp1 in osteoblast differentiation, and to test whether there is a close correlation between Nrp1 and DDR2.…”
Section: Introductionmentioning
confidence: 99%
“…2). By contrast, fenestrated rat endothelial cells of the hypothalamic-hypophyseal portal vessels release semaphorin-3A, which is thought to induce GnRH neuron axonal growth and sprouting within the ME as a function of the oestrous cycle 61 . These mechanisms are likely to enable the generation of high concentrations of GnRH, which evoke the GnRH/LH surge, to be released into the pituitary portal circulation 62,63 .…”
Section: [H3] Gnrh and Lh Surge Generationmentioning
confidence: 97%